Tasawuf antara Penafsiran Normatif dan Sosiologis dalam Pemikiran Ibn KhaldÅ«n - Abdul Kadir Riyadi (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2017)
This study takes up the challenge of investigating Ibn KhaldÅ«nâ€™s concept of tasawuf by relating it to his overwhelming idea of al-â€˜UmrÄn. The man has been widely known for his innovative assessment on various issues relating to society, organization, civilization and above all, forms of knowledge. He has been acknowledged as a pioneer and father of modern sociology. Nonetheless, little has been done to study his thought on Sufism and how this form of knowledge works in social context. Ibn KhaldÅ«n himself has not worked out to explain this problem. But one may reconstruct it within his comprehensive concept of al-â€˜UmrÄn, which is understood by some as a form of theories on social organization. It is toward this aim that this study is carried out. It argues that in Ibn KhaldÅ«nâ€™s mind, tasawuf a) is part and parcel of his notion of social organization without which a society may not emerge; and b) society has its roots not only in material, civilisational and biological needs of both man and society, but also in their spiritual needs. This spiritual need in its turns is the very motives why many undertakes spiritual quest. It is also, socially speaking, the raison deâ€™etre for social cohesion to emerge. Hence, Ibn KhaldÅ«nâ€™s sociology of tasawuf as it were, has its epistemo-logical underpinning in his implicit idea of spiritual cohesion in society.